Enhanced capacitive performance by improving the graphitized structure in carbon aerogel microspheres. Issue 37 (10th June 2020) - Liu, Xichuan; Yuan, Lei; Zhong, Minglong; Ni, Shuang; Yang, Fan; Fu, Zhibing; Xu, Xibin; Wang, Chaoyang; Tang, Yongjian
Abstract : Carbon aerogels (CAs) microspheres with good electrical conductivity and high specific surface area were synthesized by high temperature carbonization and CO2 activation method, which exhibit an enhanced capacitive performance in supercapacitors. Abstract : Herein, good electrical conductivity and high specific surface area carbon aerogel (CA) microspheres were synthesized by a facile and economical route using a high temperature carbonization and CO2 activation method. The electroconductive graphitized structure of the CA microspheres could be easily improved by increasing the carbonization temperature. Then the CA microspheres were activated with CO2 to increase the specific surface area of the electrode material for electric double layer capacitors (EDLC). The sample carbonized at 1500 °C for 0.5 h and CO2 activated at 950 °C for 8 h showed an acceptable specific surface area and excellent cycle performance and rate capability for EDLC: 98% of the initial value of the capacitance was retained after 10 000 cycles, a specific capacitance of 121 F g −1 at 0.2 A g −1 and 101 F g −1 at 2 A g −1 .